(untitled) (Research, Society and Development, 2023)
Economic crises and uncertain scenarios can intensify the process of adoption of digital technologies by companies. As an example of this adoption, there is the use of e-commerce through social media, Social Commerce (SC). The adoption of these technologies reconfigures the business model and new ways of creating value for the customer emerge. However, the literature exposes these elements and factors in a fragmented way, which makes it difficult to understand this process. The objective of this study is to propose a framework to guide the reconfiguration of the traditional or E-Commerce (EC) based business model to a SC model. Based on a Systematic Literature Review, it was possible to map the stages and identify the factors that influence SC adoption and generate value. As a result, the reconfiguration of the business model was possible due to the social interactions promoted by social media, which have web 2.0 as their base technology, which together favored commercial activities and the creation of value. From contributions to the literature, the framework presents the relationship and sequencing of the constituent elements of adoption, as well as the factors that interfere and those that create value. The model makes it easier to understand the dispersed elements that make up this reconfiguration process, and by presenting these elements in an orderly way, it provides researchers with opportunities to validate the model and develop new theories. Of the practical contributions, the pictogram is configured as a structured guide, which can help companies by showing the way to the SC implementation.